Superhydrophobic zinc oxide/epoxy coating prepared by a one-step approach for corrosion protection of carbon steel - Yap, Suk Wy; Johari, Norhasnidawani; Mazlan, Saiful Amri; Syed Ahmad, Syarifah Nur Aqida; Arifin, Rizal; Hassan, Noor Azlina; Johari, Mohd Aidy Faizal (Elsevier, 2023)
Corrosion in carbon steel (CS) has been an existing issue and it calls attention to the need for improved corrosion protection. At present, superhydrophobic (SHB) coating technology has piqued the interest of researchers as alternative means of mitigating metal corrosion. Herein, a one-step solution deposition process was used to prepare an SHB coating based on nano-zinc oxide/epoxy (ZnO/EP) on CS and its corrosion resistance performance was analyzed by the means of electrochemical analysis and compared with that of the blank CS metal and the regular coatings (plain EP and regular ZnO/EP). Results implied the as-prepared SHB coating shows remarkable improvement in corrosion protection for the substrate. Notably, it exhibited higher in both impedance modulus (|Z|) and coating resistance (Rc) results approaching 1010 Ωcm2, than those of regular coatings by 3 orders of magnitude to that of plain EP (∼107 Ω cm2), and 1 order of magnitude to regular coating (∼109 Ω cm2), indicating its superior corrosion resistance performance. Besides that, the superior inhibitive effect of the SHB ZnO/EP (ZES) is also proven by the potentiodynamic polarization (PDP) results, in which the Icorr value is suppressed down to 2.08 × 10−11 A/cm2, thereby achieving an excellent corrosion rate result of 3.38 × 10−11 mm/year. The exceptional barrier protection is ascribed to the presence of a stabilized air interlayer captured within the coating/electrolyte interface thus effectively blocking the penetration of electrolyte into the coating. This facile yet effective one-step processed SHB coating offers an effective route to improve the corrosion resistance performance of the CS metal and thereafter expand its potential applications.